Decreased heart rate variability is associated with higher levels of inflammation in middle-aged men - Lampert, Rachel (2008)
BACKGROUND: Many traditional risk factors for coronary artery disease (CAD) are associated with altered autonomic function. Inflammation may provide a link between risk factors, autonomic dysfunction, and CAD. We examined the association between heart rate variability (HRV), a measure of autonomic function, and inflammation, measured by C-reactive protein (CRP) and interleukin-6 (IL-6). METHODS: We examined 264 middle-aged male twins free of symptomatic CAD. All underwent ambulatory ECG monitoring, and 24-hour ultra-low, very-low, low, and high frequency power (ULF, VLF, LF, and HF) were calculated using power spectral analysis. CRP and IL-6 were measured and risk factors including age, smoking, hypertension, lipids, diabetes, body mass index (BMI), depression, and physical activity assessed. RESULTS: Physical activity, BMI, HDL cholesterol, smoking, depression, and hypertension were directly associated with CRP and IL-6 and inversely associated with one or more HRV variables. There was a graded inverse relationship between all HRV parameters (except HF) and CRP and IL-6. After adjustment for age, BMI, activity, HDL, smoking, hypertension, depression, and diabetes, ULF and VLF remained significant predictors of CRP (p<0.01.) CONCLUSIONS: CRP is associated with decreased HRV, even after controlling for traditional CAD risk factors. Autonomic dysregulation leading to inflammation may represent one pathway through which traditional risk factors promote development of CAD.